Unlock Your Dream: Discover the Adventure You Were Created For - Philip Wagner (WaterBrook, 2018)
Pastor and speaker Philip Wagner believes every person has been given a God-size dream to pursue, but too many have become entangled by lesser goals, losing sight of their true purpose. In Unlock Your Dream, now in trade paperback, he helps you uncover your own unique path and live with renewed expectation. With contagious passion and humor, Wagner blends biblical truths and real-world insights to invite you to: * Reach beyond the ordinary to find the extraordinary gifts God has given you * Disentangle yourself from lesser goals and embrace a God-size dream * Navigate inevitable setbacks, disappointments, and distractions * Build the ultimate team to energize your dreams with support and encouragement * Discover your true calling and forge a unique path to an adventurous life Whether you're a student, a parent, or a professional, you'll be empowered, equipped, and freed to engage in life's greatest quest: discovering and reaching God's purpose for your life. No matter your background or your life's current season, it's never too early or too late to move boldly in the direction of your dreams!